UNCO VERTEBRAL JOINTS OF LUSCHKA: AN OSTEOLOGICAL STUDY - K., Remya; Kumar, Arunachalam; Kumar, Vishal (Journal of Health and Allied Sciences NU, 2012)
Uncus or uncinate process is flange-like lip which arises from most of the lateral circumference of the upper margin of the vertebral body. It ossifies from neural arch of vertebrae. These are commonly found in lower five cervical vertebrae. The area between the periphery of intervertebral disc and uncus is occupied by loose fibrous tissue. When this fibrous tissue resorbs it leaves a space that constitutes Luschka's joint. These joints are well developed and larger in the mid to lower cervical region and smaller joints appear in the most cranial and caudal levels. We have found total of 23 such type of articular facets, on both upper and lower surfaces. These joints are clinically important because of its relationship with vessels and nerves. Many of the neurological symptoms of the arm, neck and back of the head are related to these accomadative joints
Keywords: Uncus; Cervical vertebra; Luschka's joint